Draft Annual Plan 2001 - 2002 Volume -1 - Planning Commission (Planning Commission, 2001)
Rajasthan State, in its present form, is a conglomeration of a number of princely States which varied in size, population, administrative efficiency and socio-economic development. Administratively, Rajasthan is divided today into 32 districts, which arc further sub-divided into 241 tehsils and 237 development blocks. 1.2 An area of 3.42 lakh sq. kms. of Rajasthan makes it today the largest State in the country. The tentative population of the State, according to 2001 census, is 5.65 crore. It has a long international frontier with Pakistan and is adjacent to the States of Punjab, Haryana, Uttar Pradesh. Madhya Pradesh and Gujarat. 1.3 The Aravalli Hill range runs from south-west to north-cast through the heart of the State. The region to the west and the north-west of these hills, comprises about 61.11 percent of the total area of the State and part of this forms Great Indian Desert, the 'Thar'. 1.4 As per the 2001 census (provisional), the density of population of the State is 165 persons per sq. km. as against 324 persons per sq. km. for the country as a whole. Thus human settlements in the Slate are relatively scattered. Low density of population
Narrative Government Of Rajasthan Planning Department